Tungsten trioxide integrated all-fiber phase shifter - Affendy, N.B.; Abu Bakar, M.H.; Zainol Abidin, N.H.; Muhammad, F.D.; Mustapha Kamil, Y. (Elsevier BV, 2023)
This work proposes an all-fiber phase shifter based on tapered optical fiber spin coated with tungsten trioxide (WO3). Different WO3 coating thickness was tested by varying the spin coating time from 30 to 150 s at constant 1000 rpm. Evanescent field induced by the non-adiabatic taper generated thermal optic effect through interaction with the WO3 layer, which changed its refractive index and produced phase shifting effect. The optimum spin coating time of 120 s yielded maximum phase shift of 2.52 π with wavelength shift coefficient of 0.0859 nm/mW as 980 nm pump power was varied up to 220 mW. Integration of phase shifter in fiber laser cavity produced wavelength tuning with shift coefficient of about 0.06 nm/mW. This work presents a feasible all-fiber phase shifter with simple fabrication and operation that suits current need in communication field.